2021
DOI: 10.3390/cryst11091119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectroscopy of Buckminsterfullerene Cation C60+ in a Cryogenic Ion Trapping Instrument

Abstract: The assignment of several diffuse interstellar bands in the near-infrared to C60+ ions present at high abundance in space has renewed interest in the astrochemical importance of fullerenes and analogues. Many of the latter have not been produced in macroscopic quantities, and their spectroscopic properties are not available for comparison with astronomical observations. An apparatus has been constructed that combines laser vaporisation synthesis with spectroscopic characterisation at low temperature in a cryog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Interestingly, a blue shift in the absorption wavelengths with n was observed, with a helium atom shifting the absorption bands of C 5 + by around 10 cm –1 . The same apparatus was used to spectroscopically show that the soccer ball isomer is the dominant structure with m / z = 720 produced by laser vaporization in the ion source …”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Interestingly, a blue shift in the absorption wavelengths with n was observed, with a helium atom shifting the absorption bands of C 5 + by around 10 cm –1 . The same apparatus was used to spectroscopically show that the soccer ball isomer is the dominant structure with m / z = 720 produced by laser vaporization in the ion source …”
Section: Introductionsupporting
confidence: 53%
“…The same apparatus was used to spectroscopically show that the soccer ball isomer is the dominant structure with m / z = 720 produced by laser vaporization in the ion source. 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found that the complexation of metals with fullerenes could lead to a far richer spectrum in the visible and near-infrared spectral range than fullerenes themselves, due to the charge transfer from the metal to the carbon cage, making them potential candidates for diffuse interstellar bands (DIBs). 59 The recent findings performed by Campbell et al, 60,61 about the synthesis of C 60 + ions tagged with helium and its UVvisible spectrum measurement, show experimental possibility that would support the speculations by Hou et al 19 about the charge transfer process of metallofullerenes and their contribution to the visible regime. Metals are widely known to be active catalysts for the synthetic production of various carbon nanostructures, including carbon cages under oxygen-and hydrogenrich conditions as found by Dunk et al 38,41 Then, one may speculate from the study of Hou et al 19 that metal atoms and their ions might also play a catalytic role in fullerene formation in space, as metallofullerenes, if present, could be considered as byproducts of this catalytic process.…”
Section: Gou-leimentioning
confidence: 73%
“…Sylvain Badin presented a hot topic about precise calculations of potential energy surfaces for the I + + I – → 2I reaction using an advanced relativistic electronic structure calculation in DIRAC and reaction dynamics using a semiclassical Landau-Zene dynamic method . In the hot topic of Johanna Rademacher an action spectroscopy study using helium complexes of H 2 O@C 60 + and D 2 O@C 60 + endofullerene cations was presented demonstrating much richer electronic excitation spectra than empty C 60 + cations. In the invited talk of Daniel Arismendi-Arrieta, novel approaches to iterative training in machine learning technologies were overviewed as well as benchmark calculations together with an example of an application in modeling electrolytes in emerging battery technologies.…”
Section: Conference Reportmentioning
confidence: 99%